The African Gap: Occupational Inequality of Moroccan and Sub-Saharan Immigrants in Spain, 2000-2018 - Gastón-Guiu, Silvia; Treviño, Rocío; Domingo, Andreu (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
The improvement in the labour market since 2014 has been slower for African immigrants. It widened the gap between them and other immigrants, as well as with the native Spanish population, especially among women. It raises three questions: Is this difference caused by differences in the level of education? 2) Is it a result of the concentration of African workers in low-skilled occupational niches? and, 3) specifically for women, is the incorporation of African adults into the labour market responds to a change in the generational pattern by modifying their traditional gender relationship with the labour market? We found that neither educational level nor occupational segregation are sufficient to explain the disadvantage of the African population in the labour market, especially in the face of unemployment and job insecurity and with greater severity among women. Our conclusions refer to some other extra demographic reasons that have to do with the net effect of the origin pointing out discrimination processes.